Estimation of the real burden of invasive meningococcal disease in Argentina. (2019) - Gómez, J. A.; Wetzler Malbrán, P.; Vidal, G.; Seoane, M.; Giglio, N. D.
Abstract: Among the different existing types of bacterial meningitis, the one caused by Neisseria meningitidis is the main presentation of invasive meningococcal disease (IMD). IMD is a significant public health concern and has a reported incidence rate in Argentina of 0.44 cases per 100 000 inhabitants in 2015. However, the actual incidence is thought to be higher as passive surveillance systems neither report nor identify 100% of all cases. The aim of this study is to develop an estimation of the burden of IMD in Argentina closer to reality by adjusting/correcting several limitations observed in the surveillance data available. A retrospective observational study has been performed using four Argentinean national databases recording the number of IMD cases and deaths, serogroups of N. meningitidis and ages, between 2007 to 2016. The reported data were adjusted to account for underreporting and to also integrate the cases missed due to well-known limitations associated with the diagnosis of N. meningitidis detection methods. Data were further analysed by serogroups of N. meningitidis and by age groups. After these adjustments, the potential numbers of IMD cases and IMD-related deaths are estimated to be 3.1 and 1.9 higher than reported, respectively. The study corrects the previous underestimation of the disease burden and provides expectedly more robust estimates aligned with international evidence and highlights the importance of active surveillance, with high-quality methods, for a better definition of preventive strategies against IMD in Argentina.